Evaluation of a Pharmacist-Managed Heart Failure Education Project: Empowering Patients to Self-Manage Their Disease. (June 2015) - Shepherd, Megan Riddle; Thomas, Dustin; Herald, Michael; Adane, Eyob D.
Background: Recent reimbursement cuts for hospitals with higher 30-day heart failure (HF)-related readmission rates call for means of reducing those readmissions.Objective: To determine if pharmacist-initiated education increases HF knowledge and assess if an increase in HF knowledge decreases HF readmission.Methods: This was a prospective interventional study. Participants were ≥18 years old admitted through the emergency department of a 322-bed community hospital with a diagnosis and/or past medical history of HF. Terminal/palliative care patients, patients residing in an assisted-living environment, or patients with a mental illness that deemed them incapable of participating were excluded. Forty-eight patients received pharmacist-initiated HF education on HF pathophysiology and its pharmacologic and nonpharmacologic treatment. Medication assistance and ancillary services were consulted when necessary. Patients' knowledge of HF was assessed using the same questionnaire prior to education and through a follow-up phone call within 7 days postdischarge.Results: Posteducation HF knowledge scores were 13.7 points higher than preeducation scores ( P < .05). Twenty-five patients (52%) had HF as a primary discharge diagnosis. Of those patients, 9 (36%) were readmitted within 30 days for any cause. Only 3 patients (12%) had a HF-related diagnosis at readmission. There was a statistical difference in the level of knowledge but that was not translated into a statistical difference in readmission rates.Conclusion: Patients' HF knowledge scores increased after pharmacist education. Improvements in HF knowledge could not be correlated with readmission rates. However, the majority of HF patients in this study did not have a HF-related diagnosis at the time of readmission.